Bridging the Gap: A Systematic Review of Modern Hemophilia Therapies and Global Inequities in Clinical Trial Participation - Nadiya Nurul Afifah; Lanny Indah Permatasari; Irma Rahayu Latarissa; Indra Wijaya (Haemophilia, 2026)
ABSTRACT Introduction and Objectives Hemophilia management has evolved from conventional factor replacement to non‐factor therapies and gene therapy. However, most clinical trials of modern therapies are conducted in high‐ and upper‐middle‐income countries, with limited participation from low‐ and middle‐income regions. This disparity reflects broader inequities in access to advanced treatments. This study summarizes the clinical development timeline, regulatory status, methodological approaches, and global distribution of clinical trials on modern hemophilia therapies. Methods A PRISMA‐guided systematic review was conducted using PubMed and EBSCO databases. Clinical trials evaluating gene and non‐factor therapies were identified through structured keyword searches. Titles, abstracts, and full texts were screened using predefined criteria. Data were synthesized to describe clinical progress, approval status, and geographic participation. Manual reference screening and citation tracking were also performed. Results Identified agents included gene therapies (valoctocogene roxaparvovec, etranacogene dezaparvovec; late‐stage fidanacogene elaparvovec), siRNA therapy (fitusiran), anti‐TFPI antibodies (concizumab, marstacimab), and the FVIII‐mimetic antibody emicizumab. Gene therapy is dominated by AAV platforms, offering durable expression but limited by immunogenicity, re‐dosing constraints, and high costs. SiRNA and anti‐TFPI therapies enhance thrombin generation but require careful dosing to mitigate thrombotic risk. Emicizumab provides convenient subcutaneous prophylaxis but remains costly with limited data in pediatric and resource‐limited settings. Most trials were conducted in high‐income countries, with minimal LMIC representation. Conclusion Modern therapies demonstrate strong efficacy and acceptable safety, with several approved agents. However, persistent global inequities in trial participation and access highlight the need for more inclusive research and equitable implementation strategies.